PENGARUH PENGUATAN KARAKTER ISLAM TERHADAP SIKAP TENTANG BULLYING - MIERRINA MIERRINA; SUHERMANTO JA'FAR (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2021)
During the school years, bullying is one of the most common expressions of violence in the peer context. This article present the effect of strengthening the character of Islam to the different attitudes about bullying in junior high school students. The sample were students of School with a range of early teens 12-15 years, Muslim. Taken with Purposive Random Sampling sampling technique, a total of 68 students with the criteria of research subjects are as follows: (1) Students are Muslim; (2) The age range of students is 12-15 years; (3) Having conflicting family experiences; (4) Having experiences of violence, with family and friends. This research is a quasi experimental research, with the design of One Group Pre-test - Post-test Design. Aimed at seeing differences in attitudes towards bullying shown by students before being given a reinforcement treatment of Islamic characters (pre-test) with attitudes towards bullying students after being given treatment reinforcement of Islamic characters (post-test). The statistical analysis technique used in this study is the t-test, which is to measure differences in attitudes about student bullying, between before and after treatment is given to strengthen Islamic character. The results showed a mean difference of 49,677, which means that there was a difference between the average pre-test and post-test results with a difference between 48,399 to 50,955, also known a significance value (2-tailed) of 0,000 <0.01 which means there is a very significant difference in attitudes about bullying between before and after being given reinforcement of Islamic Character.